The comparison of executive function among students with / without depression in Shiraz - Tajikzadeh, Ù‘Ù‘Fakhri; Abbasi, Fatemeh; Mohamadi, Norollah (International Journal of Applied Behavioral Sciences, 2017)
Introduction: Studies asset the effect of executive function deficit on depression disorder are growing. Therefore, the purpose of this study is comparison of the executive function in students with depression traits and non- depressed students.Methods: Ex post facto method used on 15 students with depression traits and 15 non-depressed individuals from students of academic year 2016- 2017 of Shiraz University who were selected through multi-stage random sampling. At first, 200 students was selected by multistage random sampling method from the all undergraduate students and they completed Beck Depression Inventory to select the subjects with depression and Millon clinical multiaxial inventory (MCMI III) in order to exclude subjects with personality disorder criteria. Then, we chose students with depression traits. 15 students with depression traits and 15 non-depressed students completed Wisconsin Card Sorting Test (WCST). The findings were analyzed through descriptive statistic, Multivariate variance analysis using SPSS version 16.Results: The sample ranged from 20-24 with an average age of 19.55. Results showed that students with depression traits in comparison with non- depressed students have higher perseveration error and total errors, and lower number of complete (P<0.05).Conclusion: Since deficits in cognitive performance and executive function might result in depression, attention to these factors to be modified is efficient.